Efektivitas Modul terhadap Perilaku Gizi dan Kesehatan Guru di Sekolah Menengah Makassar - Nurul Annisa; Nurhaedar Jafar; Ridwan M. Thaha (Universitas Sulawesi Barat, 2022)
Education is carried out through several media, one of them is the module. The use of modules at the time of intervention is an effective tool in educating the public. This study aims to look at changes in teacher behavior related to nutrition and health after the intervention and assess the effectiveness of using a balanced nutrition module. The research method is quasi experiment (Quasi Experiment) with the form of Non Randomized Control Group Pretest Posttest Design. The number of research sample were 92 people selected using purposive sampling method which was devided into 2 groups, namely the module group plus 46 respondents and the module group 46 respondents. The research data includes the initial data pretest and posttest of teacher behavior. The results showed that the results of paired T-test statistical tests in the module group plus there were differences in teacher knowledge before and after the intervention (p = 0.020), as well as the module group there were differences in teacher knowledge before and after the intervention (p = 0,000). For the attitude variable in the module plus group it was found that there were no differences in teacher attitudes before and after the intervention (p = 0.190) while the module group showed there were differences in teacher attitudes before and after the intervention (p = 0,000). For the action variable in the module plus group it was found that there were differences in teacher actions before and after the intervention (p = 0,000), as well as in the module group there were differences (p = 0,000). The balanced nutrition module in this study was effective because it reached the set standard limit, namely ≥ 50% of participants increased their knowledge and changed their attitudes and actions. It is recommended to teachers to improve knowledge about health and nutrition behavior.